Finding Consensus After Two Decades of Breast Implant-Associated Anaplastic Large Cell Lymphoma - Clemens, Mark W.; DeCoster, Ryan C.; Fairchild, Berry; Bessonov, Alexander A.; Santanelli di Pompeo, Fabio (Seminars in Plastic Surgery, 2019)
Breast implant-associated anaplastic large cell lymphoma (BIA-ALCL) is an emerging and indolent, but potentially fatal cancer of the immune system that can develop around textured-surface breast implants. The World Health Organization first recognized BIA-ALCL as a unique clinical entity in 2016. To date, over 600 confirmed cases have been reported worldwide. BIA-ALCL most commonly presents with disease confined to the capsule, as a seroma or a mass adjacent to the implant. While BIA-ALCL has a fairly indolent clinical course, with an excellent prognosis in early stage disease, disseminated cancer and death have also been reported. In this review, the authors focus on the early diagnosis and treatment, including reconstructing the breast following BIA-ALCL, and also discuss recently updated National Comprehensive Cancer Network guidelines. They also review the current epidemiology and risk factors associated with BIA-ALCL. Finally, they discuss important medicolegal considerations and the bioethics surrounding the continued use of textured-surface breast implants.
Keywords: breast implant-associated ALCL; anaplastic large cell lymphoma; non-Hodgkin lymphoma; CD30; double capsule; and Late Seroma